Genotypic and phenotypic traits of blaCTX-M-carrying Escherichia coli strains from an UV-C-treated wastewater effluent - Tavares, Rafael D. S. (2020)
Wastewater treatment plants (WWTPs) are relevant sources of antibiotic resistance into aquatic environments. Disinfection of WWTPs’ effluents (e.g. by UV-C irradiation) may attenuate this problem, though some clinically relevant bacteria have been shown to survive disinfection. In this study we characterized 25 CTX-M-producing Escherichia coli strains isolated from a WWTP’s UV-C-irradiated effluent, aiming to identify putative human health hazards associated with such effluents. Molecular typing indicated that the strains belong to the phylogroups A, B2 and C and clustered into 9 multilocus sequence types (STs), namely B2:ST131 (n ¼ 7), A:ST58 (n ¼ 1), A:ST155 (n ¼ 4), C:ST410 (n ¼ 2), A:ST453 (n ¼ 2), A:ST617 (n ¼ 2), A:ST744 (n ¼ 1), A:ST1284 (n ¼ 3) and a putative novel ST (n ¼ 3). PCR-screening identified 9 of the 20 antibiotic resistance genes investigated [i.e. sul1, sul2, sul3, tet(A), tet(B), blaOXA-1-like, aacA4, aacA4-cr and qnrS1]. The more prevalent were sul1, sul2 (n ¼ 15 isolates) and tet(A) (n ¼ 14 isolates). Plasmid restriction analysis indicated diverse plasmid content among strains (14 distinct profiles) and mating assays yielded cefotaxime-resistant transconjugants for 8 strains. Two of the transconjugants displayed a multi-drug resistance (MDR) phenotype. All strains were classified as cytotoxic to Vero cells (9 significantly more cytotoxic than the positive control) and 10 of 21 strains were invasive towards this cell line (including all B2:ST131 strains). The 10 strains tested against G. mellonella larvae exhibited a virulent behaviour. Twenty-four and 7 of the 25 strains produced siderophores and haemolysins, respectively. Approximately 66% of the strains formed biofilms. Genome analysis of 6 selected strains identified several virulence genes encoding toxins, siderophores, and colonizing, adhesion and invasion factors. Freshwater microcosms assays showed that after 28 days of incubation 3 out of 6 strains were still detected by cultivation and 4 strains by qPCR. Resistance phenotypes of these strains remained unaltered. Overall, we confirmed WWTP’s UV-C-treated outflow as a source of MDR and/or virulent E. coli strains, some probably capable of persisting in freshwater, and that carry conjugative antibiotic resistance plasmids. Hence, disinfected wastewater may still represent a risk for human health. More detailed evaluation of strains isolated from wastewater effluents is urgent, to design treatments that can mitigate the release of such bacteria.